Weird IR - Mislan, David Bell. author. aut Link
XI, 197 p. 4 illus. in color.
Keywords: The scholarly study of international relations tends to go over the same cases, issues, and themes. This book addresses this by challenging readers to think creatively about international politics. It highlights some of the strangest and rarest phenomena in diplomacy and world politics. Comprised of a series of vignettes and organized by common themes like nonsensical borders, quasi-countries, and diplomatic taboos, Weird IR encourages readers to think critically about the discipline without losing one's sense of humor completely. David Bell Mislan is Assistant Professor of International Studies at American University, USA. Philip Streich is Assistant Professor of Human Sciences at Osaka University, Japan.